La politique de la parole dans le rap créole : entre enjeux poétiques et engagement littéraire - Lefranc Joseph; Vinson Bradley Noël (Itinéraires)
This article examines the manifestations of the politics of speech as a constitutive element of Haitian rap. Based on interviews with rappers as well as the analysis of narrative and discursive practices observed in Haitian Rap Créole since the 1990’s, the article shows that the politics of speech has always been a constitutive element of this field of artistic and literary creation. We examine Haitian Rap Créole in terms of the idea of political engagement. We argue that although it is not possible to assert that Rap Créole is entirely political, political engagement is central to its poetics. Finally, we analyze the politicization of speech and the setting to music of political rhetoric as the two modalities of literary engagement in Rap Créole.